A Retrospective Analysis of Hematologic Parameters in Patients with Early Diabetic Kidney Disease. (March 2022) - Chen, Xu; Wang, Qinghua; Li, Chengbin
Objective: To retrospectively analyze the hematologic parameters in patients with early Diabetic Kidney Disease (DKD) to define potential biomarkers that can be used to predict early DKD. Methods: 134 diabetic patients without nephropathy and 49 patients with early DKD were enrolled for this study and the hematologic parameters were retrospectively analyzed. Paired comparison was conducted by T-test and the predicting value of any statistically different parameter was tested using the Receiver Operating Characteristic curve (ROC) analysis model. Results: The number of Neutrophil (N) was higher ( P <0.001) while monocyte (M) was lower ( P <0.01) in the early DKD group than that of DM group without nephropathy. In addition, neutrophil to lymphocyte ratio (NLR) was higher while platelet to lymphocyte ratio (PLR) was significantly lower in the early DKD group( P <0.001). Results from ROC curve analysis showed the sensitivity and specificity of PLR to predict early DKD were 83.7% and 82.6%, respectively. Conclusions: PLR may be a potential hematologic parameter that can be used to predict early DKD.